PENGARUH PENCEMARAN DAS WAY SEPUTIH DI LAMPUNG TENGAH TERHADAP SUMBER DAYA PERIKANAN (SUATU KASUS PENTINGNYA PENGELOLAAN SECARA TERPADU) (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2018)
Seputih river basin located at Center of Lampung is not only utilized by fisheries sector, but also by other sectors such as industry and water irrigation, Industrial pollution has significantly affected on the degradation of the fisheries resources and a mass mortality of cultured fish in floating cages. To cope the ecological damage caused by the pollution need am in integrated management of the river basin. Causes and effects of the pollution on the fisheries resources and their ecologies, and the importance of an integrated management of the river basin based on the community management were discussed.Keywords: river basin, pollution, fisheries, cage culture, integrated management